Immigrants Under Threat : Risk and Resistance in Deportation Nation - Prieto, Greg (Book collections on Project MUSE., 2018)
A portrait of two Mexican immigrant communities confronting threats of deportation, detention, and dispossession Everyday life as an immigrant in a deportation nation is fraught with risk, but everywhere immigrants confront repression and dispossession, they also manifest resistance in ways big and small. Immigrants Under Threat shifts the conversation from what has been done to Mexican immigrants to what they do in response. From private strategies of avoidance, to public displays of protest, immigrant resistance is animated by the massive demographic shifts that started in 1965 and an immigration enforcement regime whose unprecedented scope and intensity has made daily life increasingly perilous. Immigrants Under Threat focuses on the way the material needs of everyday life both enable and constrain participation in immigrant resistance movements. Using ethnographic research from two Mexican immigrant communities on California's Central Coast, Greg Prieto argues that immigrant communities turn inward to insulate themselves from the perceived risks of authorities and a hostile public. These barriers are overcome through the face-to-face work of social-movement organizing that transforms individual grievances into collective demands. The social movements that emerge are shaped by the local political climates in which they unfold and remain tethered to their material inspiration. Immigrants Under Threat explains that Mexican immigrants seek not to transcend, but to burrow into American institutions of law and family so that they might attain a measure of economic stability and social mobility that they have sought all along.